THE IMPORTANCE OF HYDROLOGICAL RESOURCES IN THE DEVELOPMENT OF ECOTOURISM (on the example of the Kashkadarya basin) - Yusupov, Bakhriddin Bobonazarovich; Tuychiyev, Shohimardon Abdukadirovich; Shamshiyev, Ozodbek Sindorovich (SCIENCE and SOCIETY, 2026)
The article is devoted to the issues of ecotourism opportunities and their effective use due to the landscape and natural-climatic conditions of the Kashkadarya Basin, where many unique natural monuments are located, including mountains, rivers and ancient cities.